The Impact of the Demographic and Socioeconomic Situation of the Family on their Integration into the Margins of the Cities of Beni Mellal Khenifra (Morocco): The Case of the Cities of Beni Mallal and Fquih Ben Salah - Dabarhi, Abdelghani; Mayoussi, Mohammed; Elassaad, Mohammed (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to study the impact of demographic and socioeconomic situation on the integration of families living in the margins of the cities of Beni Mellal and Fquih Ben Salah. The problem of the study was identified in the following question: How does the demographic and socioeconomic situation of the families settled by the margins of Beni Mellal and Fquih Ben Salah affect their level of integration? In order to achieve the objectives of the study and to answer the problem, two methods were adopted comparative methodology and statistical analysis, and the withdrawal of a simple random sample of households; identified in 321 families in Beni Mellal and 231 families in the city of Fquih Ben Saleh, and use the form as a tool for the study. The results of the study showed that most of the heads of households with margins in Beni Mellal and Fuih Ben Saleh are not educated, where in some marginal residential communities exceeded 50%, the results also showed the increase in the number of members of the same family (the number of members of the family sometimes 17 people) and the weak monthly income which Generally less than 1000 Moroccan dirhams (100 US dollars). The results also showed that this situation has negatively affected the integration of these families, especially at the level of connection to the drinking water and electricity network (where the proportion of households without drinking water exceeded 60%, and without electricity 50%) and construction documents such as designs and licenses (in some residential communities) There is not a single dwelling available on these documents), in addition to the low involvement of families in local environmental programs. The study recommended the need to generalize the fight against illiteracy among adults and motivate them to engage in programs monitored by the Moroccan Agency for Combating Illiteracy and Informal Education, and encourage investment in activities related to agriculture and livestock raising in order to raise family income and finally rehabilitate the margins of the two cities with environmental services and strengthen the role of civil society and facilitate administrative procedures Related to construction and thus facilitate the acceleration of family integration.
Keywords: the demographic situation; the socio-economic situation; the family; integration; the margins of cities; Beni Mellal; Faqih Ben Saleh